A high efficiency inductor‐less broadband fully integrated CMOS power amplifier. Issue 4 (25th October 2014) - Bhattacharya, Ritabrata; Basu, Ananjan; Rawat, Karun; Koul, Shiban K.
ABSTRACT: This work presents the design and implementation of a novel broadband completely inductor‐less 300 MHz–2.4 GHz power amplifier (PA) in 180 nm CMOS, primarily for applications in the ultrahigh frequency (UHF) industrial scientific and medical band. This is capable of delivering up to 15.6 dBm saturated output power with an associated peak power added efficiency of 31% in measurement. Although amplifiers with higher output power have been reported, this amplifier occupies only 0.086 mm 2 and does not require any off chip component for its operation, even at the UHF band. It also achieves the highest power density among a similar class of PA's below 10 GHz. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:311–320, 2015.